KURANG ENERGI KRONIK PADA IBU HAMIL, PEMBERIAN ASI EKSKLUSIF, DAN PENYAKIT INFEKSI (DIARE) TERHADAP KEJADIAN STUNTING PADA BALITA 24-60 BULAN DI PUSKESMAS GOGAGOMAN - Nonce Nova Legi; Muksin Pasambuna; Rivolta GM Walalangi; Yohanis Tomastola; Daniel Robert; Rudolf Boyke Purba; Elfrida Batewa (POLTEKKES KEMENKES MANADO, 2022)
ABSTRACT Stunting is a condition of failure to thrive in children under five (babies under five years old) as a result of chronic malnutrition so that the child is too short for his age. Malnutrition occurs since the baby is in the womb and in the early period after the baby is born however, the condition of stunting only appears after the baby is 2 years old. The purpose of this study was to determine the relationship of chronic energy deficiency in pregnant women, exclusive breastfeeding, and infectious diseases (diarrhea) with the incidence of stunting in infants 24-60 months in the Gogagoman Health Center. This type of research is an observational analytic study using a restropective cohort design. This study describes the relationship of chronic energy deficiency in pregnant women, exclusive breastfeeding, and infectious diseases (diarrhea) to the incidence of stunting in infants 24-60 months in the Gogagoman Health Center. This research was conducted in the working area of Gogagoman Health Center, Kotamobagu Barat, Kotamobagu City on January 23 - February 8, The sampling method was consecutive sampling with a total sample of 40 people. The results of the study using the Fisher's Exact Test showed that, there was no relationship of chronic energy deficiency (CED) in pregnant women with the incidence of stunting in infants 24-60 months in the Gogagoman Health Center obtained p value = 0.523. For exclusive breastfeeding, there is no relationship between exclusive breastfeeding and the incidence of stunting in infants 24-60 months in the Gogagoman Health Center, p = 0.454. For infectious diseases (diarrhea) that there is no relationship between infectious diseases (diarrhea) with the incidence of stunting in infants 24-60 months in Gogagoman Health Center with p = 0.477. The conclusion is that there is no correlation between chronic lack of energy in pregnant women, exclusive breastfeeding, and infectious diseases (diarrhea) with the incidence of stunting in children 24-60 months in the Gogagoman Health Center. Keywords: Chronic Energy Less, Pregnant Women, Exclusive Breastfeeding, Infectious Diseases (Diarrhea), Stunting. ABSTRAK Stunting adalah kondisi gagal tumbuh pada anak balita (bayi di bawah lima tahun) akibat dari kekurangan gizi kronis sehingga anak terlalu pendek untuk usianya. Kekurangan gizi terjadi sejak bayi dalam kandungan dan pada masa awal setelah bayi lahir akan tetapi, kondisi stunting baru nampak setelah bayi berusia 2 tahun. Tujuan penelitian yaitu untuk mengetahui hubungan kurang energi kronik pada ibu hamil, pemberian ASI Ekslusif, dan penyakit infeksi (diare) dengan kejadian stunting pada balita 24-60 bulan di Puskesmas Gogagoman. Jenis penelitian adalah penelitian observasional analitik dengan menggunakan desain kohort restropektif. Penelitian ini mendekripsikan hubungan kurang energi kronik pada ibu hamil, pemberian ASI Ekslusif, dan penyakit infeksi (diare) terhadap kejadian stunting pada balita 24-60 bulan di Puskesmas Gogagoman. Penelitian ini dilaksanakan di wilayah kerja Puskesmas Gogagoman, Kotamobagu Barat, Kota Kotamobagu tanggal 23 Januari – 08 Februari 2019. Metode pengambilan sampel yaitu consecutive sampling yang dengan jumlah sampel yaitu 40 orang. Hasil penelitian menggunakan uji Fisher’s Exact Test menunjukkan bahwa, tidak ada hubungan kurang energi kronik (KEK) pada ibu hamil dengan kejadian stunting pada balita 24-60 bulan di Puskesmas Gogagoman diperoleh nilai p=0.523. Untuk pemberian ASI Eksklusif, tidak ada hubungan pemberian ASI eksklusif dengan kejadian stunting pada balita 24-60 bulan di Puskesmas Gogagoman nilai p=0.454. Untuk penyakit infeksi (diare) bahwa tidak ada hubungan antara penyakit infeksi (diare) dengan kejadian stunting pada balita 24-60 bulan di Puskesmas Gogagoman dengan p=0.477. Dapat disimpulkan bahwa tidak terdapat hubungan kurang energi kronik pada ibu hamil, pemberian ASI Ekslusif, dan penyakit infeksi (diare) dengan kejadian stunting pada balita 24-60 bulan di Puskesmas Gogagoman. Kata Kunci : Kurang Energi Kronik, Ibu hamil, Pemberian ASI Eksklusif, Penyakit Infeksi (Diare), Stunting.